The attractiveness of Indian Polytechnics graduates—An analysis from the (demand-side) perspective of companies and colleges - Sebastian Schneider (International Journal of Training and Development, 2022)
The paper examines the attractiveness of graduates from Indian Polytechnics (PTs). The attractiveness is examined from the perspective of actors who have a demand for the graduates, namely companies and engineering colleges. To understand the reasons for their assessment of attractiveness, this study uses the concept of institutional logics (ILs) to unveil the inherent reasons behind the stakeholders' perception of attractiveness. To understand the stakeholders' ILs, interviews were undertaken in nine companies and 10 colleges in Mumbai and Delhi. The findings make clear that the companies' and colleges' assessments of the attractiveness of PT graduates are very different, reflecting their own ILs. Companies assess the attractiveness as limited due to the lack of employability of PT graduates. In contrast, colleges view graduates far more positively, as the weaknesses described by companies have less of an impact on them.
Keywords: 650